Introduction to Colloid Science: Applications to sediment characterization - Chassagne, Claire (TU Delft Open, 2021)
This book is meant as an introduction to the field of colloid science, i.e. the study of the behaviour of micrometric particles in a fluid (or a gas). The book was written with a special emphasis on sediment particles. Sediment particles are complex colloidal particles due to their composition, shape and interaction with their environment. Characterization of the colloidal fraction of sediment is done by recording, among others, the particles' size, shape and electric surface charge and evaluating their density or their interactions. These properties are important for civil engineering applications. Large-scale sediment transport models for example require as input the settling velocity of particles. In concentrated areas, this velocity becomes a function of the particles' concentration and particle-particle interactions lead to the creation of larger particles, called flocs. These flocs can settle and, when reaching the bed, consolidate in time. All these aspects, and related models, are treated in the present book.